THE CHALLANGES OF THE "PEOPLE FRONT". LEFT AND PERONISM IN THE ARGENTINE DEMOCRATIC TRANSITION - Bona, Victoria; López, Rodrigo (Revista de Historia Social y de las Mentalidades, 2020)
The “People Front” was an alliance created to participate in the 1985 legislative election and was the first experience in this field between communism and trotskyists in Argentina. At the same time that for the left the attempt to seduce the peronist workers was a priority, the importance of electoral participation and the common imagery about the binomial liberation / dependency were becoming decisive dimensions for carrying out confluence policies such as FREPU. This article recovers those essays for overcoming political and ideological differences that sometimes were irreconcilable.
Keywords: Communist Party; Movement to Socialism; Peronism; Eighties